RESPON ORANG TUA TERHADAP PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19: PARENTS' RESPONSE TO ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Atiqoh, Lia Nur (Universitas Islam Malang, 2020)
This research was conducted with the aim to find out the response of parents to online learning during pandemic Covid-19 that was recently implemented at KB-RA Mambaul Ulum. This research uses descriptive quantitative research. Data collection using a questionnaire instrument. Based on a questionnaire that has been distributed to parents, an average percentage of 74.8% is obtained. This shows that students' parents responded positively to online learning during pandemic Covid-19.Â Kata Kunci: Parent Response, Daring Learning, Pandemic Covid-19.